2015
DOI: 10.1016/j.mbs.2015.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Inference of cell–cell interactions from population density characteristics and cell trajectories on static and growing domains

Abstract: A key feature of cell migration is how cell movement is affected by cell-cell interactions. Furthermore, many cell migratory processes such as neural crest stem cell migration [Thomas and Erickson, 2008; McLennan et al., 2012] occur on growing domains or in the presence of a chemoattractant. Therefore, it is important to study interactions between migrating cells in the context of domain growth and directed motility. Here we compare discrete and continuum models describing the spatial and temporal evolution of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…It has previously been shown that different cell–cell interactions have different effects on the average displacement of agents in an ABM. 36 As may be expected, repulsive (adhesive) interactions between agents tend to increase (decrease) the average displacement of agents, and so the average displacement of agents may be a useful summary statistic for distinguishing between repulsive and adhesive cell–cell interactions in the ABM.…”
Section: Methodsmentioning
confidence: 94%
See 4 more Smart Citations
“…It has previously been shown that different cell–cell interactions have different effects on the average displacement of agents in an ABM. 36 As may be expected, repulsive (adhesive) interactions between agents tend to increase (decrease) the average displacement of agents, and so the average displacement of agents may be a useful summary statistic for distinguishing between repulsive and adhesive cell–cell interactions in the ABM.…”
Section: Methodsmentioning
confidence: 94%
“…We employ two models to simulate cell–cell interactions in the ABM, one of which has been published before. 13, 36 We define T ( v ′| v ) as the transition probability that an agent situated at site v , having been selected to move, attempts to move to site v ′, where v ′ indicates one of the nearest neighbour sites of v . Therefore, T ( v ′| v ) is only non-zero if v and v ′ are nearest neighbours.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations